Financial technology and sustainable development in ASEAN region: role of income inequality - Ahiase, Godwin; Andriana, Denny; Widyaningsih, Aristanti; Heryana, Toni; Purnomo, Budi Supriatono (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores the relationship between financial technology (FinTech), sustainable development, and the moderating role of income inequality in the Association of Southeast Asian Nations (ASEAN) countries. The study obtained data from 10 ASEAN countries from 2015 to 2022, employing a random-effects model to examine the interplay between FinTech, income inequality, and sustainable development. New findings suggest that FinTech adoption enhances environmental, economic, and social sustainability in ASEAN countries. However, this effect is enhanced by reducing the income inequality. Countries with better resource distribution employ FinTech responsibly and inclusively to improve their sustainable development. However, this study highlights the U-shaped relationship between FinTech acceptance and sustainable development. This study adds to the current body of research by emphasizing the complex impact of income inequality on the connection between FinTech and sustainable development. This finding provides a more thorough explanation of how economic disparities can shape this relationship. The findings highlight the need for policymakers and stakeholders in the financial industry to create inclusive financial ecosystems to reduce income inequality and enhance sustainable development. This includes promoting digital financial inclusion through improved internet and mobile access, enhancing financial literacy, developing robust regulatory frameworks, fostering public-private partnerships, offering targeted financial services for marginalized groups, and implementing measures to address income inequality.